Dispositifs de catégorisation et construction du lien social : l’entrée dans une association homoparentale - Luca Greco (Genre, Sexualité et Société)
In recent years, a growing number of anthropologists challenged the analytical, reflexive, and identity dimensions of fieldwork. A primary issue concerning a polyphonic, categorical, and political vision of ethnographic texts is the interactional negotiation of identities between informants and fieldworkers and its contextualization in fieldwork notes and academic texts. Drawing from fieldwork in a French gay and lesbian parents association, I will analyze how inter-subjectivity is constructed between fieldworkers and participants through the participants’ use of interactional and linguistic devices. This study will propose a vision of fieldwork as a speech event and a reflexive relationship between fieldwork, identities, and data.